Pengembangan E-LKPD Matematika Berbasis Problem Based Learning pada Materi Bangun Ruang untuk Siswa Sekolah Dasar - Dwi Sari Novianti; Muhammad Fendrik; Guslinda Guslinda (YASIN, 2026)
Although the development of electronic student worksheets (E-LKPD) and the Problem-Based Learning (PBL) model has been widely studied, research that specifically discusses their integration into interactive web-based media for mathematics learning on solid geometry in elementary schools remains limited. This study aims to describe the product design, analyze the feasibility level, and evaluate the practicality level of PBL-based mathematics E-LKPD on solid geometry for Grade V elementary school students. This study used a mixed-methods approach with a Research and Development (R&D) design through the ADDIE model, involving two expert validators and 26 students selected using purposive sampling. Data were collected using expert validation sheets and student response questionnaires, then analyzed using a percentage formula to assess feasibility and mean score calculations to assess practicality. The results showed that the developed E-LKPD obtained an average validation percentage of 93.75% in the very valid category, as well as practicality scores ranging from 3.36 to 3.50, categorized as moderately practical to practical across the four assessed aspects. These findings indicate that the Liveworksheets-based interactive E-LKPD integrated with PBL is feasible and practical for use as digital teaching material in elementary school mathematics learning. The conclusion of this study affirms the importance of integrating a problem-based approach into interactive digital worksheets to support active, contextual, and meaningful mathematics learning. The implications of this study provide theoretical contributions to the development of the digital learning media literature and practical contributions for elementary school teachers in developing interactive teaching materials aligned with learning and curriculum needs.